Elementary Technical Mathematics

Published by Brooks Cole
ISBN 10: 1285199197
ISBN 13: 978-1-28519-919-1

Chapter 6 - Review: 16

Answer

x=0.5

Work Step by Step

Simplifying 4(x + 3) + -9(x + -2) = x + 27 Reorder the terms: 4(3 + x) + -9(x + -2) = x + 27 (3 * 4 + x * 4) + -9(x + -2) = x + 27 (12 + 4x) + -9(x + -2) = x + 27 Reorder the terms: 12 + 4x + -9(-2 + x) = x + 27 12 + 4x + (-2 * -9 + x * -9) = x + 27 12 + 4x + (18 + -9x) = x + 27 Reorder the terms: 12 + 18 + 4x + -9x = x + 27 Combine like terms: 12 + 18 = 30 30 + 4x + -9x = x + 27 Combine like terms: 4x + -9x = -5x 30 + -5x = x + 27 Reorder the terms: 30 + -5x = 27 + x Solving 30 + -5x = 27 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 30 + -5x + -1x = 27 + x + -1x Combine like terms: -5x + -1x = -6x 30 + -6x = 27 + x + -1x Combine like terms: x + -1x = 0 30 + -6x = 27 + 0 30 + -6x = 27 Add '-30' to each side of the equation. 30 + -30 + -6x = 27 + -30 Combine like terms: 30 + -30 = 0 0 + -6x = 27 + -30 -6x = 27 + -30 Combine like terms: 27 + -30 = -3 -6x = -3 Divide each side by '-6'. x = 0.5 Simplifying x = 0.5
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.